Skilled migration and integration in host societies - Bermúdez Rico, Rosa Emilia (Sociedad y Economía, 2010)
the migrants qualified in host societies. In particular, interested in examining conditions that foster or hinder the employment and social integration of skilled migrant’s south-north flow. To this end, we present theoretical and analytical elements of the approach to integration of skilled and discuss the explanatory reach for the specific case of the integration of skilled migration and provide an classification scenario building in skilled migration regional contexts.